NILAI TAMBAH COCOA BUTTER DAN COCOA POWDER PADA UNIT PENGOLAHAN HASIL (UPH) SARI BUMI, KABUPATEN JEMBRANA - Dewi, Ni Luh Made Indah Murdyani; Sukendar, Ni Made Classia; Putra, I Putu Iwan Pramana (Agrifo : Jurnal Agribisnis Universitas Malikussaleh, 2024)
Cocoa is a plantation commodity that plays an important role in the regional economy. Cocoa fruit is one of the products characterized by rottenness, damage, seasonality and variety. Prevention of damage to cocoa fruit from physical, biological and chemical influences must be immediately processed into fermented cocoa beans. The fermented cocoa beans must also be immediately processed into processed chocolate products so that they can be consumed. In addition, processed chocolate also adds a higher selling value. In 2021 cocoa production in Jembrana Regency amounted to 2,949.57 tons, down from the previous year due to pest and disease attacks, unfavorable weather, and lack of intensive care. In November-December, this research was conducted at Sari Bumi UPH in Jembrana Regency with the consideration that this UPH is famous internationally with the brand Cho-Jaensan. This study used key informants from three people including the chairman and treasurer as well as cocoa processing staff. The hayami method is the value-added data analysis used in this study. Value added can be interpreted as the difference value of commodities that get special treatment (output) and the value of sacrifice (input) which is used in one production cycle. Based on the capacity of the roasting machine, UPH only processes 20 cocoa beans that have been fermented to obtain 14 kg of cocoa nibs, then produces 13 kg of cocoa paste. From 13 kg of cocoa paste, 3.25 kg of cocoa butter is produced and the rest becomes butter pulp, then it is made into cocoa powder into 7.8 kg. A total of Rp 210,000 is spent on labor costs, Rp 239,880 for variable costs/other inputs, added value of Rp 38,577.52 and processing profit of Rp 28,077.52.